Dual-task automatization: The key role of sensory–motor modality compatibility - Maquestiaux, François; Ruthruff, Eric; Defer, Alexis; Ibrahime, Stéphane (Attention, perception & psychophysics, 2018)
How do people automatize their dual-task performance through bottleneck bypassing (i.e., accomplish parallel processing of the central stages of two tasks)? In the present work we addressed this question, evaluating the impact of sensory–motor modality compatibility—the similarity in modality between the stimulus and the consequences of the response. We hypothesized that incompatible sensory–motor modalities (e.g., visual–vocal) create conflicts within modality-specific working memory subsystems, and therefore predicted that tasks producing such conflicts would be performed less automatically after practice. To probe for automaticity, we used a transfer psychological refractory period (PRP) procedure: Participants were first trained on a visual task (Exp. 1 ) or an auditory task (Exp. 2 ) by itself, which was later presented as Task 2, along with an unpracticed Task 1. The Task 1–Task 2 sensory–motor modality pairings were either compatible (visual–manual and auditory–vocal) or incompatible (visual–vocal and auditory–manual). In both experiments we found converging indicators of bottleneck bypassing (small dual-task interference and a high rate of response reversals) for compatible sensory–motor modalities, but indicators of bottlenecking (large dual-task interference and few response reversals) for incompatible sensory–motor modalities. Relatedly, the proportion of individuals able to bypass the bottleneck was high for compatible modalities but very low for incompatible modalities. We propose that dual-task automatization is within reach when the tasks rely on codes that do not compete within a working memory subsystem.